"I Should Be Closer To God Because of This" - A Case Study of Embodied Narratives and Spiritual Reconstruction in Spinal Cord Injury and Stroke Rehabilitation - Mundle, Robert (Journal of disability & religion, 2015)
This instrumental case study demonstrates the need for patients to be able to draw upon their own spiritual and religious vocabularies in order to reconstruct narrative self-continuity in the wake of debilitating illness. Through the presentation of case material taken from a series of semi-structured interviews with a 77-year-old female Roman Catholic patient who suffered a crisis of faith following a spinal cord injury and a stroke, the author illustrates key aspects of life history and religious beliefs and practices - such as lives of the saints, devotions, mystical experiences, sacred time, sacred symbols, and sacred space - to engage narrative ethics around typologies and therapeutic plots supplied by others. Narrative analysis of such discursive resources from the perspective of spiritual health can help inter-professional healthcare teams understand more fully patient needs and holistic best practices within rehabilitation environments.